Effect of heavy metals on biochemical parameters of date palm Phoenix dactylifera L. ( review article ) - Gabash, Hassanain M.; Auda, Murtada S.; Resan, Ahmed Z. (Basrah Journal Of Date Palm Research, 2023)
This article presents a comprehensive review of the effects of heavy metals on biochemical features in palm leaves. The date palm Phoenix dactylifera L. is an economically important fruit tree that is widely cultivated in arid and semi-arid regions. However, due to industrial activities and human factors, date palm plantations are increasingly exposed to heavy metal pollution in the soil. Heavy metals such as lead and cadmium have been identified as major pollutants affecting the environment and posing potential risks to human health. The review summarizes the current understanding of how exposure to heavy metals affects different biochemical features in palm fronds. It discusses the effect of heavy metals on photosynthetic pigments, antioxidant enzymes, membrane lipid oxidation, protein content, and other major biochemical characteristics. The accumulation of heavy metals in date palm leaves can disrupt photosynthetic processes, which leads to a decrease in the content of chlorophyll and carotene. Moreover, heavy metals induce oxidative stress by generating reactive oxygen species ( ROS ), which in turn influence the activities of antioxidant enzymes and increase membrane lipid peroxidation. The article also highlights the importance of studying the biochemical responses of palm leaves to heavy metal stress as potential biomarkers for monitoring and evaluation. Environmental pollution. It stresses the need for comprehensive studies to determine the threshold concentrations of heavy metals that lead to significant biochemical changes in palm fronds. Understanding these effects can help develop strategies to mitigate heavy metal pollution and its adverse effects on date palm cultivation.